If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3x + 5) * 2x = 25 Reorder the terms: (5 + 3x) * 2x = 25 Reorder the terms for easier multiplication: 2x(5 + 3x) = 25 (5 * 2x + 3x * 2x) = 25 (10x + 6x2) = 25 Solving 10x + 6x2 = 25 Solving for variable 'x'. Reorder the terms: -25 + 10x + 6x2 = 25 + -25 Combine like terms: 25 + -25 = 0 -25 + 10x + 6x2 = 0 Begin completing the square. Divide all terms by 6 the coefficient of the squared term: Divide each side by '6'. -4.166666667 + 1.666666667x + x2 = 0 Move the constant term to the right: Add '4.166666667' to each side of the equation. -4.166666667 + 1.666666667x + 4.166666667 + x2 = 0 + 4.166666667 Reorder the terms: -4.166666667 + 4.166666667 + 1.666666667x + x2 = 0 + 4.166666667 Combine like terms: -4.166666667 + 4.166666667 = 0.000000000 0.000000000 + 1.666666667x + x2 = 0 + 4.166666667 1.666666667x + x2 = 0 + 4.166666667 Combine like terms: 0 + 4.166666667 = 4.166666667 1.666666667x + x2 = 4.166666667 The x term is 1.666666667x. Take half its coefficient (0.8333333335). Square it (0.6944444447) and add it to both sides. Add '0.6944444447' to each side of the equation. 1.666666667x + 0.6944444447 + x2 = 4.166666667 + 0.6944444447 Reorder the terms: 0.6944444447 + 1.666666667x + x2 = 4.166666667 + 0.6944444447 Combine like terms: 4.166666667 + 0.6944444447 = 4.8611111117 0.6944444447 + 1.666666667x + x2 = 4.8611111117 Factor a perfect square on the left side: (x + 0.8333333335)(x + 0.8333333335) = 4.8611111117 Calculate the square root of the right side: 2.204792759 Break this problem into two subproblems by setting (x + 0.8333333335) equal to 2.204792759 and -2.204792759.Subproblem 1
x + 0.8333333335 = 2.204792759 Simplifying x + 0.8333333335 = 2.204792759 Reorder the terms: 0.8333333335 + x = 2.204792759 Solving 0.8333333335 + x = 2.204792759 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.8333333335' to each side of the equation. 0.8333333335 + -0.8333333335 + x = 2.204792759 + -0.8333333335 Combine like terms: 0.8333333335 + -0.8333333335 = 0.0000000000 0.0000000000 + x = 2.204792759 + -0.8333333335 x = 2.204792759 + -0.8333333335 Combine like terms: 2.204792759 + -0.8333333335 = 1.3714594255 x = 1.3714594255 Simplifying x = 1.3714594255Subproblem 2
x + 0.8333333335 = -2.204792759 Simplifying x + 0.8333333335 = -2.204792759 Reorder the terms: 0.8333333335 + x = -2.204792759 Solving 0.8333333335 + x = -2.204792759 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.8333333335' to each side of the equation. 0.8333333335 + -0.8333333335 + x = -2.204792759 + -0.8333333335 Combine like terms: 0.8333333335 + -0.8333333335 = 0.0000000000 0.0000000000 + x = -2.204792759 + -0.8333333335 x = -2.204792759 + -0.8333333335 Combine like terms: -2.204792759 + -0.8333333335 = -3.0381260925 x = -3.0381260925 Simplifying x = -3.0381260925Solution
The solution to the problem is based on the solutions from the subproblems. x = {1.3714594255, -3.0381260925}
| x-10=180 | | 3x+5x+2x+5=180 | | (X^2)-2XY=16 | | f(x)=8x^5+4x^4-4 | | 1(2+5x)=5 | | 7x^2-48a+64=0 | | ^24/3 | | -x-6=-6 | | n^2+7n+30=0 | | 523x=523x | | x+(3-2)=9 | | X-6=18-3x | | 9-x=25 | | 5y-1=3y+13 | | 7/12x-7/6x^2 | | 117=2x^2+7+61-x^2 | | 6y-24=12 | | 7n+21+n=37 | | 5x=65+x | | 6-(x+4)=12 | | 6y+4x=20 | | (3z-1)-(z+2)=15 | | 1.75x+0.65=10 | | 1.75-0.65x=10 | | -3e=9e+7 | | 2x1/2=9/8 | | X^2-12x-3=14 | | 3ax+1=16 | | 0.4=.40 | | 5y=16[8] | | 36=2x+y | | z/7-3=2 |